MNC Interdependence and Local Embeddedness Influences on Perceptions of Career Benefits from Global Integration - Newburry, William (Journal of International Business Studies, 2001)
This manuscript examines when global integration is perceived as being beneficial and/or detrimental to employee careers. Study results demonstrate that employees of more interdependent offices generally perceive greater career benefits from global integration, while employees of more locally embedded offices perceive negative career consequences. Hypotheses are guided by a theory of attention focus.